Constructing Collective Meaning Through Sites of Shared Reading: Determining Definitions of a Book Club Book - Pecoskie, Jen (J.L.) (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This presentation reports on a study which investigated ways reading is understood as social and/or solitary in nature. Through examination of the book club meetings (i.e., shared reading; creative and evaluative group talk), the characteristics of suitable book club books are discussed through ideas of availability, genre type, and discussibility. Cette communication porte sur une étude sur la conception et la compréhension de la lecture comme activité sociale et/ou solitaire. L’observation de rencontres d’un club de lecture (c.-à-d., des lectures partagées; des discussions créatives et évaluatives) permet de discuter des caractéristiques du choix de livres pertinents en fonction de la disponibilité du livre, du genre et du pouvoir de discussion qu’il engendre.